THE INVESTIGATION OF THE EFFECT OF VOLTAGE REGULATION DEVICES OF TRACTION SUBSTATION DC CONNECTING DEVICE - V. H. Sychenko (Nauka ta progres transportu, 2009)
Research results of voltage autocontrol devices’ ifluence on adjacent devices are considered.